Analisis Beban Pencemar dan Kapasitas Asimilasi Sungai Klinter Nganjuk: Analysis of Pollutant Load and Assimilation Capacity of Klinter River in Nganjuk - Kartikasari, Amelia Novita; Mirwan, Mohammad; Sutini, Sutini (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Klinter River in Nganjuk is subjected to pollution loads from various pollution sources, including domestic and industrial waste. Water quality can affect the condition of Klinter River, which is still used by the local community to support daily activities. The parameters analyzed include TSS, COD, BOD, NO3-, NO2-, NH3, PO4, and oil and grease, taken from data provided by the Nganjuk Environmental Agency. The study aims to assess the carrying capacity of Klinter River by analyzing pollutant loads and the river's assimilative capacity. Regression analysis is conducted to obtain equations and graphs illustrating the relationship between pollutant concentration and assimilation capacity for each parameter. The analysis results indicate that COD, BOD, and NH3 parameters are no longer able to undergo self-purification.